Hazard Stevens letter to Asahel Curtis listing prominent men involved in Mount Rainier's early history, April 20, 1914 - Stevens, Hazard, 1842-1918
Stevens wrote Curtis to respond to his request for the names of Indians or anyone else connected to early explorations of Mount Rainier. Although he cannot name any Indians, apart from his own guide, Stevens lists a number of other individuals including: "Dr. Wm. Frazer Tolmie, the Hudson Bay Co.'s factor and chief at Nisqually who used to make botanizing trips to the Mountain, of General August V. Kautz, who in 1857 made the first attempt to ascent it, of Theodore Winthrop who in his "canoe and saddle" discovered and published the Indian name of the mountain-Tacoma- of James Longmire, who with three other settlers about 1866 made a prospecting trip around the mountain." Hazard Stevens (1842-1918) was a military officer who served in the Civil War. Upon his return to Washington following the war, he made the first documented ascent of Mount Rainier on August 17, 1880 along with his partner, Philemon Beecher Van Trump. Stevens climbed the mountain again in 1905 with the Oregon mountaineering group, the Mazamas. Stevens Canyon and Stevens Ridge on Mount Rainier are both named after him.